2003
DOI: 10.2172/910973
|View full text |Cite
|
Sign up to set email alerts
|

Improved Water Flooding through Injection Brine Modification

Abstract: Crude oil/brine/rock interactions can lead to large variations in the displacement efficiency of waterflooding, by far the most widely applied method of improved oil recovery. Laboratory waterflood tests show that injection of dilute brine can increase oil recovery. Numerous fields in the Powder River basin have been waterflooded using low salinity brine (about 500 ppm) from the Madison limestone or Fox Hills sandstone. Although many uncertainties arise in the interpretation and comparison of field production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Numerous laboratory coreflood studies have shown increased oil recovery is achieved by waterflooding using low salinity water, compared with injection of seawater or high salinity produced water. [1][2][3][4][5][6] Many of these academic studies were conducted using core material and crude oil from a BP North Sea reservoir. The increase in oil recovery for low salinity water injection from this North Sea reservoir ranged from 10 to 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous laboratory coreflood studies have shown increased oil recovery is achieved by waterflooding using low salinity water, compared with injection of seawater or high salinity produced water. [1][2][3][4][5][6] Many of these academic studies were conducted using core material and crude oil from a BP North Sea reservoir. The increase in oil recovery for low salinity water injection from this North Sea reservoir ranged from 10 to 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Although Robertson et. al 7 ( Fig. 2) did not use Minnelusa reservoir core in their experimentation set, they did show that a potential increase in oil recovery could be achieved by using diluted (lower salinity) injection water with Minnelusa oil and water and Berea sandstone.…”
Section: Selection Of Fields For Waterflood Comparisonmentioning
confidence: 99%
“…7 Average recovery curves from seven corefloods are plotted in Fig. 2 and show a clear increase in recovery from low-salinity waterfloods under simulated reservoir conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Guo and Morrow, 1999; Robertson et al, 2003;Lager et al, 2006;Zhang and Morrow, 2006). It is carried out here in reference to the low salinity CO 2 -WAG in this investigation.…”
Section: Effects Of Brine Salinitymentioning
confidence: 99%